Analisis Analisis Pendekatan CRT (Culturally Responsive Teaching) Melalui Budaya Lokal Begawe Dalam Penanaman Nilai-nilai Pancasila Siswa Kelas IV SDN Barelantan - nurhayani, risya; Muhammad Husni; Yul Alfian Hadi; Rohini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of the culturally responsive teaching (CRT) approach through the local culture of Begawe in instilling Pancasila values in fourth-grade students at SDN Barelantan. The research employed a qualitative method with a narrative approach, using observation, interviews, and documentation as data collection techniwues. The findings reveal that the Begawe  tradition, as a local culture of the Sasak community, embodies values aligned with Pancasila, such as mutual cooperation, togetherness, deliberation, tolerance, and social jutice. Through the implementation of CRT, teachers lonk learning materials with students cultural experiences, making learning more contextual and meaningful. This process enhances student engagement, encourages active participation in discussions, collaboration in group work, and respect for peers opinions. Keywords: Culturally Responsive Teaching, Local Culture, Pancasila Values ABSTRAK Penelitian ini bertujuan menganalisis penerapan pendekatan Culturally Responsive Teaching (CRT) melalui budaya lokal Begawe dalam menanamkan nilai-nilai Pancasila pada siswa kelas IV SDN Barelantan. Penelitian ini menggunakan metode kualitatif dengan pendekatan naratif melalui observasi, wawncara, dan dokumentasi. Hasil penelitian menunjukan bahwa tradisi Begawe, sebagai budaya lokal masyarakat Sasak, memuat nilai-nilai yang selaras dengan Pancasila, seperti gotong royong, kebersamaan, musyawarah, toleransi, dan keadilan social. Melalui penerapan CRT, guru mengaitkan materi pelajaran dengan pengalaman budaya siswa sehingga pembelajaran menjadi kontekstual dan bermakna, proses ini meningkatkan keterlibatan siswa, mendorong mereka lebih aktif berdiskusi, bekerja sama dalam kelompok, dan menghargai pendapat teman.    Kata Kunci: Culturally Responsive Teaching, Budaya Lokal, Nilai-nilai Pancasila